GENTAMICIN POPULATION PHARMACOKINETICS IN INDIAN PEDIATRIC PATIENTS - Goda, Satyanarayana; Goda, Satyanarayana; Chodavarapu, Ravi Kumar; Devarakonda, Krishna R (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: The objective of this study was to characterize gentamicin population pharmacokinetics (PKs) in Indian pediatric patients. Methods: Population PK analysis was performed with nonlinear mixed-effect model software. The data set was inspected using both first order (FO) and FO conditional estimate (FOCE) methods by the inclusion of both patient and pathological conditions. Results: A total of 26 patients were involved in this study with 54 observations. The patient covariates, including body weight, gender, age, and creatinine clearance (CLCR), were analyzed in a stepwise fashion to identify their potential influences on gentamicin PKs. The final model gives the clearance (CL) and volume of distribution (V) by FO method as CL=Î¸1*(CLCR/35.14)+Î¸3*(WT/14.25)+Î¸5*(AGE/6.14)*EXP(Î¸1), V=Î¸2*(WT/14.25)+Î¸4*(CLCR/35.14)+Î¸6*(AGE/6.14)*EXP(Î¸2) and by FOCE method as CL=Î¸1*(CLCR/35.14+)Î¸3*(AGE/6.14)*EXP(Î¸1), V=Î¸2*(WT/14.25)+Î¸4*(CLCR/35.14)+Î¸6*(AGE/6.14)*EXP(Î¸2). Conclusion: The final model estimates of CL and V were 0.0014 L/hr/kg and 0.646 L/kg, respectively, and by FOCE method were 0.0014E-06 L/hr/kg and 0.774 L/kg, respectively. These parameters will be helpful in individualizing the loading and maintenance doses in pediatric patients. Keywords: Population pharmacokinetics, Gentamicin, Nonlinear mixed-effect model, Pediatrics.